2016
DOI: 10.1016/bs.aivir.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Nonstructural Proteins Directing Coronavirus RNA Synthesis and Processing

Abstract: Coronaviruses are animal and human pathogens that can cause lethal zoonotic infections like SARS and MERS. They have polycistronic plus-stranded RNA genomes and belong to the order Nidovirales, a diverse group of viruses for which common ancestry was inferred from the common principles underlying their genome organization and expression, and from the conservation of an array of core replicase domains, including key RNA-synthesizing enzymes. Coronavirus genomes (~26-32 kilobases) are the largest RNA genomes kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
637
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(643 citation statements)
references
References 224 publications
(475 reference statements)
0
637
0
6
Order By: Relevance
“…that most likely were acquired independently of the capping enzymes of other RNA viruses. Nidoviruses also gained ribonucleases and other accessory proteins that are involved in genome replication, virulence, and other aspects of the infection cycle of these largest known RNA viruses (61,(74)(75)(76).…”
Section: Evolution Of the 5 Major Branches Of Rna Viruses And Reconstmentioning
confidence: 99%
“…that most likely were acquired independently of the capping enzymes of other RNA viruses. Nidoviruses also gained ribonucleases and other accessory proteins that are involved in genome replication, virulence, and other aspects of the infection cycle of these largest known RNA viruses (61,(74)(75)(76).…”
Section: Evolution Of the 5 Major Branches Of Rna Viruses And Reconstmentioning
confidence: 99%
“…Cleavage of the pp1a and pp1ab polyproteins by multiple intrinsic protease activities, in combination with −1 and −2 frameshifting in the nsp2 coding region in most arteriviruses with the exception of equine arteritis virus (EAV), results in the production of 13 to 17 non-structural proteins (nsps) (Fang et al, 2012;Li et al, 2014b;Ziebuhr et al, 2000). The common ancestry of the extremely diverged nidovirus lineages is primarily reflected in the conservation of an array of 'core replicase domains' Lauber et al, 2013;Snijder et al, 2016), which is composed of two trans-membrane proteins, the viral main protease, and -encoded downstream of the ORF1a/1b frameshift site -the RNA-dependent RNA polymerase (RdRp)-and helicase-containing subunits (Fig. 1B), with the canonical RdRp domain residing in CoV nsp12 and AV nsp9.…”
Section: Introductionmentioning
confidence: 99%
“…in Sections 8 and 11 in more detail). Imaging and biochemical characterization of nidovirus nsps have shown that they are targeted to specific virus-induced membrane structures (reviewed in (Hagemeijer et al, 2012;Neuman et al, 2014;van der Hoeven et al, 2016)) where they assemble into a so-called replication and transcription complex (RTC; see (Neuman et al, 2014;Snijder et al, 2016;Subissi et al, 2014a) for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from RdRP, the other nsps coded by the replicase gene also play a crucial role in CoV replication and transcription. The nsp12 encodes the RdRP domain, nsp13 encodes the helicase (Hel) domain, while the remaining nsps encode other enzyme domain and proteins such as proteinases, a putative RNA primase, a superfamily 1 helicase, an exo-and an endoribonuclease, single-stranded RNA (ssRNA)-binding proteins, and two methyltransferases (Adedeji et al, 2012;Subissi et al, 2014;Snijder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%